1979
DOI: 10.4319/lo.1979.24.5.0940
|View full text |Cite
|
Sign up to set email alerts
|

Body size patterns in arctic and temperate zooplankton1

Abstract: Do zooplankton species occur in discrete associations of large and small species? In 36 arctic tundra ponds near Barrow, Alaska, there were 21 examples of a large species association, 9 of a small association, and 6 intermediate associations. Statistically, the species do show evidence of nonrandom association. The literature of comparative examples is used to investigate the significance of intermediate species associations in the arctic ponds and elsewhere. Intermediates are found to occur, and in some cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The difference was attributed to the level of fish predation-absent in the large zooplankton lakes and intense in the small zooplankton lakes. Dodson (1979) discussed the two lake types, and concluded that there also can be ''intermediate species associations'' with a range of body sizes and that in some locations they can make up a large portion of observed communities. Gillooly & Dodson (2000) surveyed over 1,100 lakes from 80°N to 77°S, and found a wide range of mean body sizes among cladocerans.…”
Section: Community Characteristicsmentioning
confidence: 98%
“…The difference was attributed to the level of fish predation-absent in the large zooplankton lakes and intense in the small zooplankton lakes. Dodson (1979) discussed the two lake types, and concluded that there also can be ''intermediate species associations'' with a range of body sizes and that in some locations they can make up a large portion of observed communities. Gillooly & Dodson (2000) surveyed over 1,100 lakes from 80°N to 77°S, and found a wide range of mean body sizes among cladocerans.…”
Section: Community Characteristicsmentioning
confidence: 98%
“…Size selective predation is a major factor that determines the composition of zooplankton species asso-0 (Brooks & Dodson, 1965 ;Dodson, 1979) . Plankton-eating fish tend to remove the larger species (Brooks & Dodson, 1965) .…”
Section: Species Associationsmentioning
confidence: 99%
“…Small species tend to occur either in lakes with intense fish predation and large species occur in lakes with little or no fish predation (Dodson, 1979) . We hypothesized that the same would be true in Aguascalientes .…”
Section: Introductionmentioning
confidence: 99%
“…The zooplankton community in tundra ponds may be quite diverse (Dodson, 1979;Stross et al (1980). However, most ponds are frequently predominated by associations of only a few species.…”
Section: Effects Of Various Environmental Factors On Phytoplankton Sementioning
confidence: 99%
“…However, most ponds are frequently predominated by associations of only a few species. Generally they are characterized by relatively larger species, such as Daphnia middendorffiana Fischer and Heterocope septentrionalis Juday & Muttkowski or by smaller species, such as Daphnia pulex Leydig (Dodson, 1979). At Barrow, Alaska, Daphnia middendorffiana is the dominant species .…”
Section: Effects Of Various Environmental Factors On Phytoplankton Sementioning
confidence: 99%